The emerging trend of non-operative treatment in paediatric type I open forearm fractures. (August 2017) - Zhang, H.; Fanelli, M.; Adams, C.; Graham, J.; Seeley, M.
Purpose: Open fractures are considered an orthopaedic emergency and are generally an indication for operative debridement. Recent studies have questioned this approach for the management of Gustilo-Anderson Type I open fractures in the paediatric population. This meta-analysis studies the non-operative management of Type I open paediatric forearm fractures. Methods: An Ovid MEDLINE and PubMed database literature search was performed for studies that involved a quantified number of Gustilo-Anderson Type I open forearm fractures in the paediatric population, which were treated without operative intervention. A fixed-effect meta-analysis, weighting each study based on the number of patients, and a pooled estimate of infection risk (with 95% confidence interval (CI)) was performed. Results: The search results yielded five studies that were eligible for inclusion. No included patients had operative debridement and all were treated with antibiotics. The number of patients in each study ranged from 3 to 45, with a total of 127 paediatric patients in the meta-analysis. The infection rate was 0% for all patients included. The meta-analysis estimated a pooled infection risk of 0% (95% CI 0 to 2.9). Conclusions: The five included studies had a total of 127 patients with no cases of infection after non-operative management of Type I open paediatric forearm fractures. The infection rate of Type I fractures among operatively managed patients is 1.9%. The trend in literature towards non-operative treatment of paediatric Type I open fractures holds true in this meta-analysis.